2018
DOI: 10.1177/0892705718785678
|View full text |Cite
|
Sign up to set email alerts
|

Flammability and thermal properties of modified carbon nanotubes in poly(lactic acid)

Abstract: The multi-walled carbon nanotubes (CNTs) were modified using phosphaphenanthrene compounds (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO)) and vinyl triethoxy silane (VTES) by covalent bond. The DOPO- and VTES-treated CNTs were named DVCNT, and the structure was characterized by Fourier transform infrared, thermogravimetric analysis, and transmission electron microscopy. Nanocomposites were prepared by adding CNTs or DVCNT to poly(lactic acid) (PLA), and the flame retardancy was examined by determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The formation of the intumescent char layer was due to uniform dispersion of APP after coating on the one hand and the surface treatment agent PCOC acting as the carbon source on the other hand; so the carbon layer presented a typical morphology of the intumescent char layer. It is well known that the char layer can block the transfer of oxygen and heat, which decreased the combustion intensity of materials (Chen et al, 2016;Chen et al, 2017c;Li et al, 2018;Guo et al, 2019;Xu et al, 2019). From Table 4, the char yield of RPUF/MAPP-1000 reached 36.5% at 400 s. The results indicated that MAPP-1000 with a high degree of polymerization was more conducive to promoting the formation of the intumescent char layer with higher thermal stability.…”
Section: Flame-retardant Performance Of Rpuf Compositesmentioning
confidence: 88%
“…The formation of the intumescent char layer was due to uniform dispersion of APP after coating on the one hand and the surface treatment agent PCOC acting as the carbon source on the other hand; so the carbon layer presented a typical morphology of the intumescent char layer. It is well known that the char layer can block the transfer of oxygen and heat, which decreased the combustion intensity of materials (Chen et al, 2016;Chen et al, 2017c;Li et al, 2018;Guo et al, 2019;Xu et al, 2019). From Table 4, the char yield of RPUF/MAPP-1000 reached 36.5% at 400 s. The results indicated that MAPP-1000 with a high degree of polymerization was more conducive to promoting the formation of the intumescent char layer with higher thermal stability.…”
Section: Flame-retardant Performance Of Rpuf Compositesmentioning
confidence: 88%
“…Biopolymers show low LOI values because they are highly flammable and ignitable. For instance, the LOI reported for PLA was 19% [156] and 19.5%, [155] and 21% for PBS. [164] However, other reported LOI values are greater than 21% for neat biopolymers, for example, the reported LOI values of PBAT were 22.8% [165] and 24.5% for PBS.…”
Section: Flammability Propertiesmentioning
confidence: 99%
“…This has been mostly carried through the incorporation of flame-retardant materials such as intumescent flame retardants, nitrogen and phosphorus-based compounds, inorganic and organic materials, and halogencontaining compounds. [153][154][155] Nevertheless, halogenbased flame retardants have the disadvantage of releasing toxic gases and increases smoke release; hence, they are no longer favorable. [154] Although flame retardants are efficient in improving the flame resistance of polymers, large amounts are required, which occurs at the expense of other properties.…”
Section: Flammability Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Covalent functionalization can significantly improve the overall thermal performance for carbon nanotube-reinforced polymer nanocomposites due to a great increase in the thermal conductance of the interface [229,231]. However, excessive chemical functionalization will damage the intrinsic thermal properties of carbon nanotubes [244][245][246][247].…”
Section: Characterization Of Interfacialmentioning
confidence: 99%